2018
DOI: 10.1590/s1980-220x2017004303289
|View full text |Cite
|
Sign up to set email alerts
|

Supporting in grief and burnout of the nursing team from pediatric units in Chilean hospitals

Abstract: Objective To know the levels of Burnout Syndrome and perception of grief support in nursing teams of oncology and pediatric intensive care in public hospitals in Chile. Method A study of descriptive cross-sectional design. The Maslach Burnout Inventory and the Grief Support Health Care Scale were applied to university-level and technical nursing professionals between March and November 2015. An analysis to compare the means was performed with use of the Student's t-test, and the level of significance was set a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 18 publications
2
9
0
7
Order By: Relevance
“…In other studies, childless status was found to be related to increased D among younger nurses [34]. Edmonds et al [36] observed that young nurses presented higher levels of EE than older ones; on the other hand, burnout has also been associated with being 40 years or more [34,39,41]. In relation to organisational and other occupational factors, Reyes-Marrero et al [40] reported an association between burnout and a relative lack of professional experience, while Liakopoulou et al [40] found this same factor to be associated with increased D. For Gallagher and Gormley [37], the three dimensions of burnout were related to inexperience, i.e., the lower the level of experience, the greater the EE and D and the lower PA.…”
Section: Risk Factors For Burnout In Paediatric Oncology Nursesmentioning
confidence: 69%
See 4 more Smart Citations
“…In other studies, childless status was found to be related to increased D among younger nurses [34]. Edmonds et al [36] observed that young nurses presented higher levels of EE than older ones; on the other hand, burnout has also been associated with being 40 years or more [34,39,41]. In relation to organisational and other occupational factors, Reyes-Marrero et al [40] reported an association between burnout and a relative lack of professional experience, while Liakopoulou et al [40] found this same factor to be associated with increased D. For Gallagher and Gormley [37], the three dimensions of burnout were related to inexperience, i.e., the lower the level of experience, the greater the EE and D and the lower PA.…”
Section: Risk Factors For Burnout In Paediatric Oncology Nursesmentioning
confidence: 69%
“…Finally, a low prevalence of PA (which is measured in the inverse sense to that of the other dimensions) under 20% was only found in two studies [37,41], which reported values of 13.3% and 16.7%, respectively, while the remaining studies obtained higher values, ranging from 22.8 to 41% [34][35][36]38]. The above findings are presented in detail in Table 1.…”
Section: Burnout Prevalence and Meta-analytical Estimationmentioning
confidence: 88%
See 3 more Smart Citations